The - Millyard, Anne W.
Once upon a time, a very long time, there was an emperor. And this emperor owned so many fancy clothes that he could have supplied everyone at a very big Halloween party with a costume! The emperor received merchants from around the world who offered him fancy fabrics, silks and satins... But one day, three gentlemen arrived with a fabric so magical that it had to remain top secret!